INTELLIGENT SYSTEMS FOR DIGITAL EXHIBITION DESIGN - Goyal, Gopal; Faiz, Ayaan; Narayana, Ananta; Dev, Anoop; L, Yashoda L; Kurulekar, Mahesh (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The study evaluates the evolution and the use of smart systems in designing digital exhibits with the key aspects of how artificial intelligence (AI), machine learning, and immersive technologies can redefine the conventional exhibition models into responsive, interactive, and data-driven cultural experiences. Combining computational intelligence with the human imagination, the study shows that AI-aided curation can boost aesthetic expression, as well as visitor interests and involvement, by means of personalization in terms of storytelling, real-time feedback, and adaptation to emotions. The empirical foundation of analysis includes three case studies, namely, a virtual museum prototype, a hybrid physical-digital exhibition, and a cultural heritage restoration project. Quantitative results present the fact that user satisfaction, engagement, and curatorial efficiency significantly increase, whereas qualitative data shows that audiences resonate more with digital artifacts. The model of AI–curator cooperation in the current study will guarantee the implementation of the human interpretive judgment as the core of the research, with the algorithms supplementing the design decisions with the pattern recognition and predictive learning processes. The paper will conclude that intelligent exhibitions are a new cultural mediation paradigm, in which technology and creativity merge to create experiences of inclusive, sustainable and ethically responsible art. The potential topics to be considered in future studies are emotion-aware storytelling, simulation of exhibitions using digital twins and low-energy adaptive displays to promote scalability and cultural consistency of next-generation museums.